Small fatigue crack growth behavior of Ti-6Al-4V produced via selective laser melting: In situ characterization of a 3D crack tip interactions with defects. (August 2020) - Waddell, Michael; Walker, Kevin; Bandyopadhyay, Ritwik; Kapoor, Kartik; Mallory, Alexandra; Xiao, Xianghui; Chuang, Andrew C.; Liu, Qianchu; Phan, Nam; Sangid, Michael D.
Highlights: Small fatigue crack growth behavior of additive manufactured Ti-6Al-4V is examined. In situ tomography provides information regarding crack interactions with defects. In situ energy dispersive X-ray diffraction measures strains ahead of the crack tip. Slower fatigue crack growth rates are observed for small cracks. Faster fatigue crack growth rates are observed for samples from optimal builds. Abstract: Small fatigue crack growth (SFCG) behavior is examined for additively manufactured Ti-6Al-4V specimens with optimal and trial build conditions (representing an increased degree of defects) through a combination of in situ tomography and in situ energy dispersive X-ray diffraction. The results showed slower crack growth rates for the SFCG samples compared to the long cracks (which was not expected). In the case of the trial conditions, the increased levels of porosity deterred crack growth by blunting the crack, as evident by the in situ tomography characterization.